2021
DOI: 10.1002/fsn3.2426
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nano‐zinc oxide morphology on functional and antibacterial properties of tapioca starch bionanocomposite

Abstract: Petroleum polymers have significant thermal, inhibitory, and mechanical properties and relatively low price and easy processing capability. Therefore, these polymers are widely used in the pack-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 67 publications
4
24
0
6
Order By: Relevance
“…Desam et al [18] further confirmed the antibacterial activity of peppermint essential oil against E. coli. The antibacterial activity of ZnO nanoparticles in different bionanocomposite films has been confirmed by other researchers [20,22,53].…”
Section: Effects Of Zno-n and Meo On The Antibacterial Activity Of Gelatin Filmssupporting
confidence: 61%
See 2 more Smart Citations
“…Desam et al [18] further confirmed the antibacterial activity of peppermint essential oil against E. coli. The antibacterial activity of ZnO nanoparticles in different bionanocomposite films has been confirmed by other researchers [20,22,53].…”
Section: Effects Of Zno-n and Meo On The Antibacterial Activity Of Gelatin Filmssupporting
confidence: 61%
“…Another group of additives used to improve the physical, chemical, and functional properties of biocomposite edible films is nanoscale fillers, primarily inorganic nanoparticles, such as silver, clay, TiO 2 , SiO 2, and ZnO [20,21]. The barrier, mechanical, antioxidant, and antimicrobial properties and thermal stability of biocomposite films reinforced with these nanoparticles have improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starch is one of the most common wall materials for the encapsulation process because they are safe, nontoxic, available, inexpensive, and biodegradable (Aminian et al., 2013; Tamimi et al., 2021). Tragacanth (Katira) is a heterogeneous resinous polysaccharide with a highly branched structure that is resistant to acid.…”
Section: Introductionmentioning
confidence: 99%
“…Tapioca starch has a low price, high viscosity, bland flavor, clear paste appearance, and low pasting temperature than other starches. Therefore, this starch has wide applications in the food industry (Sheng et al, 2018;Tamimi et al, 2021).Since native starches have some undesirable properties such as retrogradation, syneresis, and low water holding capacity…”
mentioning
confidence: 99%